#### Question

Write the discriminant of the following quadratic equations:

(*x* − 1) (2*x* − 1) = 0

#### Solution

We have been given, (*x* − 1) (2*x* − 1) = 0

Now, simplify the equation to be represented in the quadratic form, so we have

2x^{2} - x - 2x + 1 = 0

2x^{2} - 3x + 1 = 0

Now we also know that for an equation ax^{2} + bx + c = 0, the discriminant is given by the following equation:

D = b^{2} - 4ac

Now, according to the equation given to us, we have,a = 2, b = -3 and c = 1.

Therefore, the discriminant is given as,

D = (-3)^{2} - 4(2)(1)

= 9 - 8

= 1

Therefore, the discriminant of the equation is 1.

Is there an error in this question or solution?

Advertisement

Advertisement

Write the Discriminant of the Following Quadratic Equations: (X − 1) (2x − 1) = 0 Concept: Relationship Between Discriminant and Nature of Roots.

Advertisement